2009
DOI: 10.1097/01.ncq.0000347451.28794.38
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Change-of-Shift Report

Abstract: This article describes a clinical nurse-led initiative that changed the traditional group shift report in the conference room to a combination of a written report with a nurse-to-nurse verbal exchange at the patient's bedside. The new process resulted in less time spent in shift report, financial savings from reduced overtime, and a decrease in the number of patient falls and call lights during change of shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 4 publications
0
52
1
2
Order By: Relevance
“…This result is consistent with findings of other research confirming increases in patients' sense of safety. 1,3,7,13,17 The bedside handover should not be conducted as a report from one member of staff to the other but should involve an interaction between the patient and the staff of the two shifts. The nurse is not obliged to inform the patient of his/her diagnosis, rather accompanying him/her along the way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings of other research confirming increases in patients' sense of safety. 1,3,7,13,17 The bedside handover should not be conducted as a report from one member of staff to the other but should involve an interaction between the patient and the staff of the two shifts. The nurse is not obliged to inform the patient of his/her diagnosis, rather accompanying him/her along the way.…”
Section: Discussionmentioning
confidence: 99%
“…A more precise assessment of the various aspects of this method for the change of shift would require the collection of data over an adequate period on the following indicators: time spent during the handover in the patient's bedroom including time per individual patient and total for all patients, time spent in the nurses' room again both for each individual patient and the total for all patients, the number and type of interruptions in the nurses' room, and the number and type of interruptions in the patients' bedrooms. 13 It has to be recognized as a limitation of the study that the data collected did not cover these indicators, capable of providing further insight into the effectiveness and efficiency of the implementation, highlighting the involvement of the various players, and establishing the degree to which the project was successful. Not all the potential benefits of the bedside handover were covered in the questionnaires.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Meade and colleagues (7) found that the incorporation of hourly nursing rounds on nursing units lead to both a decreased use of call lights and a decreased patient falls by anticipating patients' needs. Similarly, a study by Athwal and colleagues (8) concluded that improvements in communication during it the most common extrinsic risk factor for patient falls in that unit. Call lights not being answered on time (meaning quickly enough to meet the needs of an individual patient) were found to be contributing factors to a significant number of falls on the unit (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Con un promedio de tiempo determinado para su desarrollo de 15 a 45 minutos, que varía según el número de pacientes y su condición, este es uno de los retos más reafirmados en los profesionales de enfermería para mantenerse dentro del marco de tiempo asignado (4) . Athwal et al y Hays han abordado principalmente el tipo, la duración, el contenido o características, sus ventajas y desventajas (2,12) , así como, pruebas con cambios en el proceso frente al paciente y su familia (13) . Riesenberg et al hacen hincapié en la complejidad del informe y las dificultades, como la falta de comunicación y la trasferencia inadecuada de los cuidados (14) .…”
Section: Características Del Cambio De Turnounclassified
“…-Normalización; la normalización es otra estrategia que influye positivamente en el proceso, el uso de bitácoras o formatos estandarizados (12) para la información tiene un uso frecuente y facilita o disminuye la posible variabilidad en la comunicación del reporte. Así mismo, se puede trabajar con los pacientes y las familias para determinar qué otros aspectos del cuidado deben ser incluidos en la plantilla del informe.…”
Section: Estrategias Para Mejorar El Recibo Y Entrega De Turnounclassified